Перспективы создания новой природоохранной территории в Маневичском районе Волынской области (Украина) - Кузьмишина, Ірина Іванівна; Коцун, Лариса Олександрівна; Войтюк, Василь Петрович; Коцун, Борис Борисович; Kuzmyshyna, Iryna I.; Kotsun, Larysa O.; Voitiuk, Vasyl P.; Kotsun, Borys B. (Брестский государственный технический университет, 2016)
For protection of the coenopopulation of the species Jovibarba globifera (L.) J. Parn. listed in the Red Book of Ukraine, creation of the branch "Boridnyk" area of 0,3 ha from the landscape reserve of local importance "Kashivskyy" (Manevichy district, Kovel forestry) is proposed.
Keywords: Бородник шароносный Jovibarba globifera; место нахождения; новая природоохранная территория; Маневичский район; Волынская область